SOME RESULTS FOR SOLUTION AND FOCAL POINTS OF NONSELFADJOINT SECOND ORDER SYSTEMS (Journal of Sciences, Islamic Republic of Iran)
Consider y" (t) + A (t)y (t) + 0, y is a real n-dimensinal vector and A(t) is a real nxn matrix, continuous on some interval. Some positivity properties of solutions and conjugate points of y"(t) + A(t)y (t) = 0 appeared in literature. We prove similar results for focal points